Komparasi Lembaga Pengawas Perlindungan Konsumen di Indonesia dan Jepang - Yolanda Hasanah, Sandria (UNES Law Review, 2023)
Efficiency between authority and the burden of duties and responsibilities in improving consumer protection needs to be continuously updated both in terms of regulations and institutions. As a comparison country, Japan is considered the right country to make comparisons, especially in the field of supervision of the financial services sector, where Japan as a developed country has experienced many regulatory and institutional transformations, so this discussion is futuristic in nature. Japan itself had new consumer protection regulations in 1994, while consumer protection regulations in Indonesia are regulated in Law No. 8 of 1999. This research is normative juridical research with a computational approach and a statutory-regulatory approach. The results of this research show specific consumer protection in the financial services sector, both have almost the same instruments and institutions, OJK (Financial Services Authority) and BI (Bank Indonesia) in Indonesia, while in Japan there is the Financial Services Agency (OJK) and the Central Bank . Japan (BOJ), the difference is that the supervision process is carried out (on-site inspection), whereas in Indonesia it is still based on coordination based on the authority of each institution.